Ectoparasites of buffaloes (Bubalus bubalis) in Kurigram district of Bangladesh - Mamun, MAA; Begum, N; Shahadat, HM; Mondal, MMH (Journal of the Bangladesh Agricultural University, 2010)
Epidemiology of ectoparasites of buffaloes was studied in Kurigram district of Bangladesh from November, 2007 to October, 2008. A total of 236 buffaloes were examined, among them 61.86% were found infested with one or more species of ectoparasites. Three species of ectoparasites were identified of which, two species were arachnids, namely, Boophilus microplus (13.98%), Haemaphysalis bispinosa (11.44%) and one species was insect, namely, Haematopinus tuberculatus (51.27%). No mites were detected. Among the ectoparasites, mixed infection was common. In this investigation, prevalence of ectoparasites in relation to age, sex and seasonal dynamics were also studied. Ectoparasitic prevalence was higher (p<0.01) in winter season (80.00%) followed by summer (50.68%) and rainy (39.62%) seasons. Significantly (p<0.01) higher prevalence of ectoparasites were recorded in female animals (85.71%) than in males (56.70%). In the age groups, buffalo calves aged 0.5-2 years (73.68%) were mostly susceptible (p<0.01) to ectoparasites than young aged > 2-5 years (70.73%) and adult animals aged >5 years (58.52%). Overall mean ectoparasitic burden was 2.31±1.31 per square inch of heavily infested area. The highest parasitic burden was recorded in case of H. tuberculatus (3.49±2.29) followed by B. microplus (1.85±0.94) and H. bispinosa (1.59±0.69). It is concluded that, ectoparasites are the common threat to Buffalo rearing in Kurigram district of Bangladesh irrespective of age and sex of the buffaloes and seasons of the year. Keywords: Ectoparasites; Epidemiology; Buffalo; Kurigram district DOI: 10.3329/jbau.v8i1.6400 J. Bangladesh Agril. Univ. 8(1): 61–66, 2010